User Satisfaction Analysis of Online Public Access Catalog Using End User Computing Satisfaction Method - Dista Trianisfi; Nurfaizah Nurfaizah; Eka Tripustikasari (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2021)
Libraries are organizations with the activities of collecting, processing, disseminating, preserving, and presenting information that in which the Online Public Access Catalog (OPAC) have been widely adopted. However, the analysis of OPAC satisfaction is still rare. This study discusses the analysis of user satisfaction of OPAC. This study aims to determine the effect of content dimensions, accuracy, format, ease of use, and timeliness using the End User Computing Satisfaction (EUCS) method, a method for measuring the level of user satisfaction of a system. SPSS software was used to analyze user satisfaction. Sig. value of the content variable is greater than 0.1 (0.667), hence the hypothesis zero (H0) is accepted. It means that the content variable has no effect on user satisfaction. Sig. value for the accuracy variable is less than 0.1 (0.009), hence the H0 is rejected. Therefore, the accuracy variable has an effect on user satisfaction. Sig. value of the format variable is less than 0.1 (0.054), hence H0 was rejected, implying that the format variable has an effect on user satisfaction. Sig. value of the ease of use variable is greater than 0.1 (0.700), hence H0 is accepted, meaning that the ease of use variable has no effect on user satisfaction. Sig. value of the timeliness variable was 0.120 (> 0.1), hence H0 is accepted. Therefore, the timeliness variable has no effect on user satisfaction.